Whey Protein Isolate Film and Laser-Ablated Textured PDMS-Based Single-Electrode Triboelectric Nanogenerator for Pressure-Sensor Application - Minwoo Lee; Jonghwan Shin; Sunkook Kim; Srinivas Gandla (Sensors, 2022)
The use of biopolymers for realizing economical and eco-friendly triboelectric nanogenerators (TENGs) widens the application prospects of TENGs. Herein, an animal-sourced whey protein isolate (WPI) film, processed and prepared by a simple aqueous solution preparation and drop-casting technique, is applied to demonstrate its potential use in bio-TENGs. With the addition of formaldehyde in WPI, the films result in a free-standing and flexible film, whereas the pure WPI films are difficult to handle and lack flexibility. A TENG device based on the WPI and the laser-ablated textured polydimethylsiloxane (PDMS) for pressure-sensor application were developed. The output voltage of the TENG comprising WPI increased nearly two-fold compared to the TENG without WPI. A simple single-electrode TENG device configuration was adopted so that it could be easily integrated into a wearable electronic device. Moreover, WPI film exhibited tribo-negative-like material characteristics. This study provides new insights into the development of biocompatible and eco-friendly biopolymers for various electronic devices and sensors.